2000
DOI: 10.1074/jbc.275.2.992
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Classes of Phosphatidylinositol 3′-Kinases Are Involved in Signaling Pathways That Control Macroautophagy in HT-29 Cells

Abstract: 3-Methyladenine which stops macroautophagy at the sequestration step in mammalian cells also inhibits the phosphoinositide 3-kinase (PI3K) activity raising the possibility that PI3K signaling controls the macroautophagic pathway (Blommaart, E. F. C., Krause, U., Schellens, J. P. M., Vreeling-Sindelá rová , H., and Meijer, A. J. Macroautophagy is a major intralysosomal catabolic process conserved during the evolution of eukaryotic cells (1-4). In mammalian cells, the macroautophagic pathway starts with the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
879
6
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,098 publications
(925 citation statements)
references
References 60 publications
33
879
6
7
Order By: Relevance
“…Class I PI3K is involved in inhibitory effect on autophagy, while the class III PI3K is involved in the sequestration of cytoplasmic material in autophagy. 31 Therefore, we suggest that the effect of 3-MA on TMZ-induced autophagy may be due to inhibition of the class III PI3K. Bafilomycin A1 is a specific inhibitor of the lysosomal protein pump (vacuolar H þ -ATPase).…”
Section: Discussionmentioning
confidence: 89%
“…Class I PI3K is involved in inhibitory effect on autophagy, while the class III PI3K is involved in the sequestration of cytoplasmic material in autophagy. 31 Therefore, we suggest that the effect of 3-MA on TMZ-induced autophagy may be due to inhibition of the class III PI3K. Bafilomycin A1 is a specific inhibitor of the lysosomal protein pump (vacuolar H þ -ATPase).…”
Section: Discussionmentioning
confidence: 89%
“…Wortmannin and LY294002 bind to the catalytic subunit of PI 3-kinase, while 3-MA interacts with the regulatory subunit. 15 The consistent results obtained with three different PI 3-kinase inhibitors argue that PI 3-kinase Cell Death and Differentiation (2004) 11,[1146][1147][1148][1149] activates programmed degradation of the parental macronucleus and unexchanged pronuclei.…”
mentioning
confidence: 86%
“…These experiments have shown that the product of class-III PI3K, phosphatidylinositol 3-phosphate (PI(3)P), is required for autophagy, whereas the products of class-I PI3K, phosphatidylinositol 3,4, bisphosphate (PI(3,4)P 2 ), and phosphatidylinositol-3,4,5-trisphosphate (PI(3,4,5)P 3 ), have inhibitory effects. 27 Indeed, overexpression of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), which removes the phosphate from the 3-position of PI(3,4)P 2 and PI(3,4,5)P 3 , increases autophagy. 28 The PI3K inhibitors do not distinguish between class-I and -III PI3K, and also inhibit the formation of PI(3)P, and thus inhibit autophagy.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 99%